2008
DOI: 10.1097/qad.0b013e3282f20a77
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic myocardial ischaemia in HIV-infected adults

Abstract: ECG evidence of asymptomatic IHD was common in this large cohort of HIV-infected adults and more common than a history of symptomatic IHD. Traditional factors were the predominant determinants of risk. No clear association between ART type or duration and asymptomatic IHD was noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…A recent cohort study found that 40% of HIV-infected individuals were smokers [30], compared with 27% of the Danish population as a whole in 2006 [31]. This difference is small and could not have accounted for our findings.…”
Section: Discussionmentioning
confidence: 61%
“…A recent cohort study found that 40% of HIV-infected individuals were smokers [30], compared with 27% of the Danish population as a whole in 2006 [31]. This difference is small and could not have accounted for our findings.…”
Section: Discussionmentioning
confidence: 61%
“…In the Strategies for Management of Antiretroviral Therapy Study, interruption of antiretroviral treatment was associated with an increased short-term risk of cardiovascular disease, 27 and a high proportion of asymptomatic myocardial ischemia was found in HIVinfected adults, irrespective of their antiretroviral treatment status. 28 In another study, HIV patients who had not initiated antiretroviral treatment had a higher risk of hospitalization for ischemic heart disease than a population-based control group. 29 Pathogenetic research supports the direct role of HIV in accelerating arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest HIV infection as a potentially relevant contributor to arteriosclerosis and provide a conceptual background for the increased cardiovascular risk observed among HIV-infected individuals regardless of antiretroviral treatment. 28,29 Close, noninvasive evaluation of preclinical atherosclerotic disease should be considered for HIV patients, especially those with additional risk factors for cardiovascular diseases, with the aim of addressing intensive lifestyle and pharmacological interventions aimed at reducing cardiovascular risk.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…By comparison, the risk increased 32% for each additional year of age, and was 280% greater for current tobacco smokers (compared with nonsmokers) and 74% greater for persons with a BMI greater than 30 compared with a BMI of 18 to 26 [35•]. Carr et al [38], for the SMART study, also confi rmed that traditional factors were the predominant determinants of risk for asymptomatic myocardial ischemia events in that study.…”
Section: Cardiovascular Disease and Metabolic Abnormalitiesmentioning
confidence: 89%